PENGARUH BRAND IMAGE, PRICE PERCEPTION, DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN LITTLE TALK BISTRO FATMAWATI - Widya Intan Warapsari; Efiani MM (Politeknik Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of brand image, perceived price and service quality on purchasing decisions at Little Talk Bistro. This research uses quantitative descriptive methods. In this study with a consumer population at Little Talk Bistro of 100 respondents. The sample technique used accidental sampling technique. data collection techniques used by researchers are questionnaire methods with a Likert scale where researchers process multiple linear regression data with the help of the IBM SPSS 26 application. The results of the study partially brand image, price perception and service quality have a positive effect on purchasing decisions, and there is a simultaneous influence brand image, price perception and service quality have a significant effect on purchasing decisions.